Effect and Risks with Insertion of Vaginal Foreign Bodies in the Pediatric and Adolescent age - Shamayal Mandokhel, Zahida Kamal, Habibullah Babar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The children and adolescent reporting vaginal injury due to foreign object insertion are reported as 4% of the cases visiting a gynecological outpatient department. Most common symptoms observed are the bleeding or foul-smelling vagina with abnormal discharge. Objective: To assess the effect and risks with insertion of vaginal foreign bodies in the pediatric and adolescent age. Study Design: Retrospective study Place and Duration of Study: Balochistan Institute of Child Health Services Quetta from 1st June 2021 to 30th June 2023. Methodology: Five hundred children and adolescent visiting the Balochistan institute of child health services OPD or emergency unit were enrolled in this study. The inclusion criteria was considered all those children and adolescent girls between the age group of 6-15 years with vaginal discharge and discomfort and diagnosed as cases of foreign body insertion in their vagina. A complete clinical assessment as well as demographic details of each patient was registered. The clinical details regarding physical and psychosocial assessments as well as the type of object used for insertion was conducted through a well-structured questionnaire. Results: The mean age of the patients was 7.5±3.2 years. Majority of children and adolescent had inserted magnetic beads/hard items in their vagina followed by batteries or other mechanical devices. The Physical /Psychosocial examination of patients showed 42% had performed self-induction while 35% were anxiety driven cases. Out of the total number of patients 182/500 had vaginal bleeding, while 144/500 had fowl smell and vaginal discharge. Pain and fever was recorded in 115/500 cases. Ultrasonography seems to have 79% sensitivity and an effective method for identification of foreign body in vaginal track. The recent study also analyzed the consequences of vaginal foreign body insertion and found 94% cases to have bacterial infection (S with those cases which were delayed having septicemia and long term treatment requirement of antibiotics for their bacterial infection. Surgical intervention was performed in almost all cases. In 3% cases had fistula formation. Conclusion: In children and young adolescent females presenting recurrent or persistent vaginal discharge the risk of such insertion includes severe bacterial infection and even septicemia. Keywords: Effect, Risk, Vaginal foreign body, Pediatrics